Internal and External Barriers to Energy Efficiency: Made-to-Measure Policy Interventions - Cristina Cattaneo (Fondazione Eni Enrico Mattei (FEEM), 2018)
This paper has two objectives. First it provides a correlation between internal and external barriers to energy efficiency and consumer behaviour related to two domains. It evaluates behaviour related to energy curtailment, which represents routine, repetitive effort to decrease consumption on a day-to-day basis. It also considers behaviour related to investments, which are one time actions such as purchasing new energy efficiency technologies.. Second, it assesses the effectiveness of the different interventions and programs in addressing the two types of barriers (internal and external) with the aim of informing the policy debate. By assessing the value of a large number of interventions, this paper is one of the first that combines in a unified framework the main findings of different disciplines, from economics to psychology.
Keywords: D9; Q4; Q48; 330; Energy Efficiency; Energy Policy; Behavioural Economics